Clade-Specific Evolution Mediated by HLA-B*57/5801 in Human Immunodeficiency Virus Type 1 Clade A1 p24 - McKinnon, Lyle R. (American Society for Microbiology (ASM), 2009)
HLA-B*57-mediated selection pressure leads to a typical escape pathway in human immunodeficiency virus type 1 (HIV-1) CD8 epitopes such as TW10. Whether this T242N pathway is shared by all clades remains unknown. We therefore assessed the nature of HLA-B*57 selection in a large, observational Kenyan cohort where clades A1 and D predominate. While T242N was ubiquitous in clade D HLA-B*57(+) subjects, this mutation was rare (15%) in clade A1. Instead, P243T and I247L were selected by clade A1-infected HLA-B*57 subjects but not by HLA-B*5801(+) subjects. Our data suggest that clade A1 consensus proline at Gag residue 243 might represent an inherent block to T242N escape in clade A1. We confirmed immunologically that P243T and I247L likely represent escape mutations. HLA-B*57 evolution also differed between clades in the KF11 and IW9 epitopes. A better understanding of clade-specific evolution is important for the development of HIV vaccines in regions with multiple clades.